Age of the Donor Reduces the Ability of Human Adipose‐Derived Stem Cells to Alleviate Symptoms in the Experimental Autoimmune Encephalomyelitis Mouse Model. (9th September 2013) - Scruggs, Brittni A.; Semon, Julie A.; Zhang, Xiujuan; Zhang, Shijia; Bowles, Annie C.; Pandey, Amitabh C.; Imhof, Kathleen M.P.; Kalueff, Allan V.; Gimble, Jeffrey M.; Bunnell, Bruce A.
Abstract : In a mouse model, human adipose‐derived mesenchymal stem cells from older donors failed to ameliorate the neurodegeneration associated with experimental autoimmune encephalomyelitis, and mice treated with cells from older donors had increased central nervous system inflammation, demyelination, and splenocyte proliferation. The age‐related therapeutic differences corroborate recent findings that biologic aging occurs in stem cells. Abstract : There is a significant clinical need for effective therapies for primary progressive multiple sclerosis, which presents later in life (i.e., older than 50 years) and has symptoms that increase in severity without remission. With autologous mesenchymal stem cell therapy now in the early phases of clinical trials for all forms of multiple sclerosis (MS), it is necessary to determine whether autologous stem cells from older donors have therapeutic effectiveness. In this study, the therapeutic efficacy of human adipose‐derived mesenchymal stem cells (ASCs) from older donors was directly compared with that of cells from younger donors for disease prevention. Mice were induced with chronic experimental autoimmune encephalomyelitis (EAE) using the myelin oligodendrocyte glycoprotein35–55 peptide and treated before disease onset with ASCs derived from younger (<35 years) or older (>60 years) donors. ASCs from older donors failed to ameliorate the neurodegeneration associated with EAE, and mice treated with older donor cells had increased central nervous system inflammation, demyelination, and splenocyte proliferation in vitro compared with the mice receiving cells from younger donors. Therefore, the results of this study demonstrated that donor age significantly affects the ability of human ASCs to provide neuroprotection, immunomodulation, and/or remyelination in EAE mice. The age‐related therapeutic differences corroborate recent findings that biologic aging occurs in stem cells, and the differences are supported by evidence in this study that older ASCs, compared with younger donor cells, secrete less hepatocyte growth factor and other bioactive molecules when stimulated in vitro. These results highlight the need for evaluation of autologous ASCs derived from older patients when used as therapy for MS.